Lowering the tone in art and science collaboration: An analysis from science and technology studies. Issue 1 (1st March 2019) - Sleigh, Charlotte; Craske, Sarah; Park, Simon
This article analyses a collaborative project in art and science (A&S) from a science and technology studies (STS) perspective. In so doing, it reorientates discussion of the affinity between these two disciplines away from abstract epistemology and towards pragmatic questions in the areas of expertise, credit, space, institutions and money.